Cyberbullying, Problematic Internet Use, and Psychopathologic Symptoms among Korean Youth - Jung, Young-Eun; Leventhal, Bennett; Kim, Young Shin; Park, Tae Won; Lee, Sheen-Hoo; Lee, Myeongmi; Park, Seon Hee; Yang, Jong-Chul; Chung, Young-Chul; Chung, Sang-Keun; Park, Jong-Il (Yonsei medical journal, 2014)
To evaluate the associations between cyberbullying behaviors and problematic internet use, and to compare psychopathologic symptoms in victims, perpetrators, and victims-perpetrators of cyberbullying to those in youths who were not involved in cyberbullying. A total of 4531 youths (11-14 years of age) were recruited from elementary and middle schools. Among 4531 youths, 9.7% were involved in cyberbullying; 3.3% were only victims; 3.4% were only perpetrators; and 3.0% were victims-perpetrators. Cyberbullying behaviors were associated with problematic internet use as well as various psychopathologic symptoms. Depressive symptoms were associated with cyberbullying victimization, and rule-breaking behaviors and aggressive behaviors have relevance to cyberbullying perpetration. Greater attention needs to be paid to identify youths earlier who are involved in cyberbullying and prevent serious adverse consequences in them.